Phytoalexin deficient 4 is associated with the lesion mimic trait in watermelon clalm mutant (Citrullus lanatus) - Jiale Shi; Congji Yang; Yuanyuan Qin; Qingqing Liu; Shengqi Hua; Defeng Wu; Wei Dong (BMC Plant Biology)
Abstract In watermelon (Citrullus lanatus), lesion mimic is a rare, valuable trait that can be used by breeders for selection at early growth stages. In this study, we tested a seven-generation family to determine the inheritance and genetic basis of this trait. As revealed by analysis of the lesion mimic mutant clalm, this trait is controlled by a single dominant gene. Whole genome resequencing–bulked segregant analysis demonstrated that this gene is located on chromosome 4 from 3,760,000 bp to 7,440,000 bp, a region corresponding to a physical distance of 3.68 Mb encompassing approximately 72 annotated genes. There are 6 genes with non-synonymous mutation SNP sites. The predicted target gene, ClCG04G001930, encodes a Phytoalexin deficient 4 (PAD4), a protein that plays an important regulatory role in leaf senescence in many plant species. According to quantitative real-time PCR analysis, the expression level of ClCG04G001930 was significantly higher in the clalm mutant than in normal watermelon. Twenty-five SNPs were identified in the ClCG04G001930 gene of F2 individuals of the clalm mutant. Overexpression the ClCG04G001930 gene, designated as ClPAD4, yielded transgenic lines whose leaves gradually developed chlorotic lesions over 3 weeks. RNA interference of the ClPAD4 yielded transgenic lines whose cotyledon prone to diseased over 2 weeks. Our results suggest that ClPAD4 might be the candidate gene responsible for lesion mimic in the clalm mutant. Our findings may serve as a foundation for elucidating the mechanism underlying the molecular metabolism of programmed cell death and should be useful for marker-assisted selection breeding in watermelon.